Pregabalin Add-On vs. Dose Increase in Levetiracetam Add-On Treatment: A Real-Life Trial in Dogs With Drug-Resistant Epilepsy - Kriechbaumer, Sandra R. P.; Jurina, Konrad; Wielaender, Franziska; Schenk, Henning C.; Steinberg, Tanja A.; Reese, Sven; Buhmann, Gesine; Doerfelt, Stefanie; Potschka, Heidrun; Fischer, Andrea (Frontiers in Veterinary Science, 2022)
Epilepsy is a common neurological disorder affecting 0.6 % to 0.75 % of dogs in veterinary practice. Treatment is complicated by the occurrence of drug-resistant epilepsy in up to 30 % of dogs with idiopathic epilepsy and appearance of cluster seizures. Only few controlled studies are available to guide treatment choices beyond licenced veterinary drugs. The aim of the study was to compare antiseizure efficacy and tolerability of two treatment strategies in dogs with drug-resistant idiopathic epilepsy. Study design was a prospective open label comparative treatment trial. Treatment success was defined as 3fold extension of the longest baseline interseizure interval and to a minimum of three months. To avoid prolonged adherence to a presumably ineffective treatment strategy dog owners could leave the study after the third day with generalized seizures if the interseizure interval failed to show a relevant increase. Twenty-six dogs (mean age 5.5 years, mean seizure frequency 4/month) with drug-resistant idiopathic epilepsy and a history of cluster seizures were included. Dogs received either add-on treatment with pregabalin 4 mg/kg twice daily (14 dogs) or a further increase in levetiracetam dosage (12 dogs). Thirteen dogs in the pregabalin group had drug levels within the therapeutic range for humans, and dogs treated with pregabalin had increased sedation scores compared to levetiracetam (p < 0.041). Two dogs in the pregabalin group (14.3 %; 2/14) and one dog in the levetiracetam group (8.3 %; 1/12) achieved treatment success with long seizure free intervals from 122 to 219 days, but then relapsed to their initial seizure frequency ten months after study inclusion. The overall low success rates with both treatment strategies likely reflect a real-life situation in canine drug-resistant idiopathic epilepsy in everyday veterinary practice. These results delineate the need for research in better pharmacologic and non-pharmacologic treatment strategies in dogs with drug-resistant epilepsy.